2011
DOI: 10.1080/09603123.2011.572278
|View full text |Cite
|
Sign up to set email alerts
|

Detection of potential risk of wastewater effluents for transmission of antibiotic resistance from Vibrio species as a reservoir in a peri-urban community in South Africa

Abstract: We assessed the antibiogram characteristics of some Vibrio species isolated from wastewater final effluents in a typical peri-urban community of South Africa. Marked resistances were noted against erythromycin (100%), chloramphenicol (100%), nitrofurantoin, cefuroxime and cephalothin (90-95%) in V. parahaemolyticus, V. fluvialis and V. vulnificus, respectively. Fourteen antibiotypes were identified, with multiresistance to 8-10 antibiotics being common. The antibiotypes AMP, PEN, STR, SUL, TMP, COT, CHL, ERY, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…isolates was conducted using boiling method [15]. Briefly, pure isolates were obtained from the sorbitol-MacConkey agar, and these colonies were inoculated on sorbitol-MacConkey agar to ensure purity, from which the resulting pure colonies were further grown on nutrient agar prior to DNA extraction.…”
Section: Dna Extractionmentioning
confidence: 99%
“…isolates was conducted using boiling method [15]. Briefly, pure isolates were obtained from the sorbitol-MacConkey agar, and these colonies were inoculated on sorbitol-MacConkey agar to ensure purity, from which the resulting pure colonies were further grown on nutrient agar prior to DNA extraction.…”
Section: Dna Extractionmentioning
confidence: 99%
“…This is largely due to its food-borne nature ability to cause mild to moderate dehydration, vomiting, fever, abdominal pain, and diarrhea (18,19). It was first isolated in 1977 from a patient suffering from severe diarrhea (18) and can be frequently detected in both human diarrheal stool samples and aquatic environments (20,21). It has been reported that V. fluvialis elicits intestinal fluid when fed to suckling mice (22) and produces an array of virulence factors, including proteases, cytolysins, and toxins that elongate Chinese hamster ovary (CHO) cells (23,24).…”
mentioning
confidence: 99%
“…This has resulted to increased resistance to different antibiotics groups. Vibrio specie is not an exception when it comes to antibiotic resistant strains [1,3] several studies have reported the appearance of such strains. The development of antibiotic resistance outpaces the development of new drugs such that it has become a global challenge with detrimental long term effects [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these water bodies are used for drinking water, household, recreational purposes and fishing by the people living in the surrounding communities and they are at risk of acquiring Vibrio infections [2]. Vibrio species and other food-borne pathogens that have been exposed to antibiotics within or outside the effluents environment, can acquire antibiotics resistance transferable by mobile genetic elements and horizontal gene transfer [1]. This has resulted to increased resistance to different antibiotics groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation